DEVELOPMENT OF CONTEXTUAL TEACHING AND LEARNING-BASED IPA STUDENT WORKSHEETS TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS - Ebet Elbita Tarigan; Nurdin Hill; Naeklan Simbolon (Jurnal Ilmiah Teunuleh, 2022)
The purpose of this study is to determine the feasibility and effectiveness of developing worksheets for science students based on contextual teaching and learning (CTL) to improve critical thinking skills. This research method is development research. The sample of this study was a grade V student of Binjai Methodist Private Elementary School. The data analysis techniques in this study are descriptive studies and t-tests. The results of the research and conclusions in this study are: 1) For the feasibility test in this development research, namely the expert validation test conducted on 3 experts, namely Indonesian experts, material experts and learning media experts. obtained a score by an expert Indonesian of 35 with a percentage of 72.92% (quite valid), then a score was obtained by a material expert where the score was obtained 55 with a percentage of 85.94% (Valid). Then a score was obtained by a learning media expert of 64 with a percentage of 69.75% (quite valid). The results of the field trial in this study were obtained the number of scores obtained from 28 students, the average score obtained was 49.07 with a percentage of 87.63% (Valid) 2. For the effectiveness test, from the results of the calculation of the data obtained tcount = 8.34 From the distribution list t using the odds of 1-? = 0.95 with dk n-1 (27-1) = 26 obtained the price ttable = 4.25. So that tcount > ttable is obtained, thus the hypothesis states "There is an effectiveness of a Contextual Teaching and Learning (CTL) Based Science Student Worksheet on the "Heat Transfer" material in Class V of Binjai Methodist Private Elementary School"